MENUMBUHKAN KERUKUNAN DALAM HIDUP BERAGAMA MENURUT PANDANGAN AGAMA KATOLIK - Andreas Suparto (Bahasa Indonesia, 2018)
Present, many people talk on intereligious dialogue at various levels, formally or informally in order to create a peaceful society. In line with it, Indonesian Government create the intereligious dialogue at various lavels. But in reality, there are often conflict between reality and what the Government want to. This article try to contribute some ideas to awake the catholics in order to create peaceful inter religious dialogue. It focuses on how to understand and developt intereligious dialogue as a new evangelization.